A brief review on the mechanisms and approaches of silk spinning-inspired biofabrication - Mu, Xuan; Amouzandeh, Reza; Vogts, Hannah; Luallen, Elise; Arzani, Milad (Frontiers in Bioengineering and Biotechnology, 2023)
Silk spinning, observed in spiders and insects, exhibits a remarkable biological source of inspiration for advanced polymer fabrications. Because of the systems design, silk spinning represents a holistic and circular approach to sustainable polymer fabrication, characterized by renewable resources, ambient and aqueous processing conditions, and fully recyclable "wastes." Also, silk spinning results in structures that are characterized by the combination of monolithic proteinaceous composition and mechanical strength, as well as demonstrate tunable degradation profiles and minimal immunogenicity, thus making it a viable alternative to most synthetic polymers for the development of advanced biomedical devices. However, the fundamental mechanisms of silk spinning remain incompletely understood, thus impeding the efforts to harness the advantageous properties of silk spinning. Here, we present a concise and timely review of several essential features of silk spinning, including the molecular designs of silk proteins and the solvent cues along the spinning apparatus. The solvent cues, including salt ions, pH, and water content, are suggested to direct the hierarchical assembly of silk proteins and thus play a central role in silk spinning. We also discuss several hypotheses on the roles of solvent cues to provide a relatively comprehensive analysis and to identify the current knowledge gap. We then review the state-of-the-art bioinspired fabrications with silk proteins, including fiber spinning and additive approaches/three-dimensional (3D) printing. An emphasis throughout the article is placed on the universal characteristics of silk spinning developed through millions of years of individual evolution pathways in spiders and silkworms. This review serves as a stepping stone for future research endeavors, facilitating the in vitro recapitulation of silk spinning and advancing the field of bioinspired polymer fabrication.